“INSUFICIENCIA JURÍDICA PARA PROTEGER EL PAGO DE ALIMENTOS A FAVOR DE LOS HIJOS EN EL CÓDIGO DE LA NIÑEZ Y ADOLESCENCIA” - Costa Cacay, Nelly Karina (2021)
The present research presented under the thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem that is identified. Against the Resolution of the Constitutional Court No. 012-27-NI-CC that limits the personal constraints of debtors in fulfilling their maintenance obligations, it is necessary to establish in the Code of Children and Adolescents differentaspects to consider so that The Judge may order the personal urgency and not meet the requirement of the delinquent to pay the pensions owed in comfortable monthly installments that constitute an attack on the superior interest of the child. I consider it necessary to establish in the Code of Children and Adolescents,that the measure of urgency dictated by the Judge, is carried out when the amount of the settlement due is for a period of more than one year, in addition to an absence total by the parent, accruing in carelessness and abandonment regarding their responsibilities towards the child. These facts must be considered by the Judge equal to the provisions of the Constitutional Court Resolution no.012-17-SIN-CC, and for legal certainty must be stipulated in the Childhood and Adolescence Code